Jenis Fasiliti Keselamatan Bangunan Kediaman Berstrata - Md Ariffin, Khadijah; Manos, Wani Zarifah; Omar, Abdul Jalil (Research in Management of Technology and Business, 2023)
Safety facilities are one of the facilities provided in a stratified building. Although there are guidelines for the provision of these facilities, there are still differences in the types of facilities provided in stratified buildings. Therefore, this study was performed to identify the types of security facilities that are available in a multi-level building. This study uses systematic literature review method to obtain data. The data obtained from the literature review were collected and analyzed using the thematic method. The results of the study found that there are 12 types of safety facilities provided in stratified buildings. Among them is fire extinguishers, fire-alarm systems, fire-sprinkler systems, smoke detectors, fire doors, fire-rated walls and partitions, closed-circuit television (CCTV), fence, emergency lighting, emergency exit sign, security system and security signs. It is hoped that the results of this study can help with more in-depth studies related to the management of security facilities in stratified buildings in the future.